Implementasi Sorogan Dalam Pembelajaran Al-Qur’an Pada Madrasah Diniyah Takmiliyah - Muhammad Musodiqin; Difla Nadjih; Taufik Nugroho (Universitas Cokroaminoto Yogyakarta, 2017)
Sorogan method is the main learning strategy in Islamic boarding schools, including when teaching the Koran. The implementation was not very different from the Madrasah Diniyah (Primary School established by the ministry of religious affairs in 1964 to study only Islamic religious sciences), especially in the Diniyah Takmiliyah Faidlul Barokat Madrasah (MDTFB). The results of the study indicate that there have been efforts made by caregivers to overcome the inhibiting factors of the Koran's learning and to consider its supporting factors. Suggestions intended for each student, parent guardian and caregiver teacher can then be given.